Bonnie and clyde eaudiobook The lives behind the legend. - Schneider, Paul (Tantor Media, 2009)
In Paul Schneider's hands, the legend behind the daring movie that revolutionized Hollywood becomes the true story of Bonnie and Clyde. Told in the lovers' own voices, it offers verisimilitude and drama to match Truman Capote's In Cold Blood . Strictly nonfiction—no dialogue or other material has been made up—and set in the dirt-poor Texas landscape that spawned the star-crossed outlaws, the brilliantly researched and dramatically crafted tale opens with a murderous jail break and ends with the ambush and shoot-out that consigned their bullet-riddled bodies to the front seat of a hopped-up getaway car. Bonnie Parker and Clyde Barrow's relationship was, at the core, a toxic combination of infatuation blended with an instinct for going too far too fast. The poetry-writing, petite Bonnie and her diminutive, gun-crazy lover (she at four feet, ten inches tall, he barely 125 pounds) drove lawmen wild, slipping the noose every single time. That is, until their infamy caught up with them in the famous ambush that literally blasted away their four years of live-action rampage in seconds. Without glamorizing the killers or vilifying the cops, this book, alive with action and high-level entertainment, provides a complete picture of America's most famous outlaw couple and the culture that created them.